Social issues in ICT project implementation in the local authorities of Selangor, Malaysia / Rugayah Hashim - Hashim, Rugayah (Research Management Institute (RMI), 2010)
This paper seeks to provide insights of social issues in implementing ICT based projects in twelve local authorities of Selangor; Malaysia. It also describes a framework of social in hibitors of ICT project implementation. In the study, this framework mergeda number of sub-issues to construct a broader higher-level schema in information system planning, procurement and execution. Deploying a mixed method approach, the analyses highlighted eight sub-issues, which are, human resource, organizational environment, organizational culture. organizational directives, management process. interdepartmental coordination. organizational support and resistance to change. The identification ofthese social inhibitors would provide a better path to successful implementation of ICT projects by local authorities. As the ICT implementation framework is relatively new. guidelines and examples were also identified to manage the difficulties and profundities of executing ICT initiatives.